Evaluate 9⁴ × 3⁻⁸ × (1/3): Complete Exponent Simplification

Question

943813=? 9^4\cdot3^{-8}\cdot\frac{1}{3}=\text{?}

Video Solution

Solution Steps

00:00 Simplify the following problem
00:03 Let's break down 9 to 3 squared
00:06 Let's substitute this into our exercise
00:13 Number (A) raised to a negative power (N)
00:17 Equals 1 divided by the number (A) raised to the same exponent (N)
00:23 We'll apply this formula to our exercise to convert a fraction into a base
00:28 When there's a power over a power, the combined power is the product of the powers
00:34 We'll apply this formula to our exercise
00:42 Let's calculate the powers
00:47 When multiplying powers with equal bases
00:50 The power of the result equals the sum of the powers
00:53 We'll apply this formula to our exercise
00:57 Let's calculate the power
01:00 This is the solution

Step-by-Step Solution

First let's note that the number 9 is a power of the number 3:

9=32 9=3^2

therefore we can immediately move to a unified base in the problem, in addition we'll recall the law of powers for negative exponents but in the opposite direction:

1an=an \frac{1}{a^n} =a^{-n}

Let's apply this to the problem:

943813=(32)43831 9^4\cdot3^{-8}\cdot\frac{1}{3}=(3^2)^4\cdot3^{-8}\cdot3^{-1}

where in the first term of the multiplication we replaced the number 9 with a power of 3, according to the relationship mentioned earlier, and simultaneously the third term in the multiplication we expressed as a term with a negative exponent according to the aforementioned law of exponents.

Now let's recall two additional laws of exponents:

a. The law of exponents for power of a power:

(am)n=amn (a^m)^n=a^{m\cdot n}

b. The law of exponents for multiplication between terms with equal bases:

aman=am+n a^m\cdot a^n=a^{m+n}

Let's apply these two laws to the expression we got in the last stage:

(32)43831=3243831=383831=38+(8)+(1)=3881=31 (3^2)^4\cdot3^{-8}\cdot3^{-1}=3^{2\cdot4}\cdot3^{-8}\cdot3^{-1}=3^8\cdot3^{-8}\cdot3^{-1}=3^{8+(-8)+(-1)}=3^{8-8-1}=3^{-1}

where in the first stage we applied the law of exponents for power of a power mentioned in a', in the next stage we applied the law of exponents for multiplication of terms with identical bases mentioned in b', then we simplified the resulting expression.

Let's summarize the solution steps, we got that:

943813=(32)43831=38+(8)+(1)=3881=31 9^4\cdot3^{-8}\cdot\frac{1}{3}=(3^2)^4\cdot3^{-8}\cdot3^{-1} =3^{8+(-8)+(-1)}=3^{8-8-1}=3^{-1}

Therefore the correct answer is answer b'.

Answer

31 3^{-1}